An Investigation of Norm of Belief’s Proper Formulation - Seyyed Ali Kalantari (Journal of Philosophical Investigations, 2017)
That falsity is a defect in belief can be captured with a prohibitive norm holding that truth is the necessary condition for permissibility of belief. Furthermore, such a formulation avoids the difficulties encountered in earlier literature that offered prescriptive norms. The normativity of belief thesis is widely discussed in the literature. I criticise bi-conditional formulation of the norm of the normativity of belief thesis which holds that truth is both the necessary and sufficient condition for the permissibility of belief formation. I argue that the part which holds that truth is the sufficient condition for the permissibility of belief formation is redundant. The argument follows from clarifying the key ideas at stake in the normativity of belief thesis, namely, that false belief is a defect and that the normativity thesis is supposed to distinguish the concept of belief from other cognitive attitudes and the slogan that belief aims at truth.